The substrate of criminal-legal influence - Козаченко, Олександр Васильович; Козаченко, О. В.; Козаченко, Александр Васильевич; Kozachenko, Oleksandr V.; Сотула, Олександр Сергійович; Сотула, О. С.; Сотула, Александр Сергеевич; Sotula, Oleksandr S.; Бібленко, Василь Станіславович; Бібленко, В. С.; Библенко, Василий Станиславович; Biblenko, Vasyl S.; et al. (Universidad del Zulia, 2021)
The aim of the article is found on the idea of measure as a substrate of criminal-legal influence. The publication proposes to consider the measure as a substrate of external forms of legal influence and criminal-legal measure as a primary element of all external forms of criminal-legal influence (in connection with the commission of a criminal act). The analysis allows us to conclude that the substrate of legal influence is a basic element of socio-legal regulation (which substantively combines a system of techniques and methods of influence used to obtain a positive and socially significant result). It should be understood that a criminal-legal measure is a system of techniques and methods of coercive and rehabilitation-encouraging influence of the state on criminal practices (criminal offenses, objectively illegal acts, abuse of law) and lawful post-criminal behavior, which is carried out by the law, determined by the socio-cultural environment. It is concluded that such ideas of Leonardo Polo as coexistence, the abandonment of mental limit, his thoughts on ethics, knowledge, and law can be applied successfully when the criminal-legal measure is characterized by several features that distinguish it from measures of the legal influence of another industry.

Метою статті є уявлення про захід як субстрат кримінально-правового впливу. Публікація пропонує розглядати захід як субстрат зовнішніх форм правового впливу та кримінально-правовий захід як первинний елемент усіх зовнішніх форм кримінально-правового впливу (у зв’язку з вчиненням злочинного діяння). Проведений аналіз дозволяє зробити висновок, що субстрат правового впливу є базовим елементом соціально-правового регулювання (який змістовно поєднує в собі систему прийомів і методів впливу, що використовуються для отримання позитивного та соціально значимого результату). Слід розуміти, що кримінально-правовий захід – це система прийомів і методів примусового та реабілітаційно-заохочувального впливу держави на злочинні дії (кримінальні правопорушення, об’єктивно протиправні діяння, зловживання правом) та правомірну посткримінальну поведінку, які здійснюється законом, що визначається соціокультурним середовищем. Зроблено висновок, що такі ідеї Леонардо Поло, як співіснування, відмова від розумової межі, його думки про етику, знання, право можуть успішно застосовуватися, коли кримінально-правовий захід характеризується кількома ознаками, що відрізняють його від правових заходів іншої галузі.
Kozachenko O. The substrate of criminal-legal influence / O. Kozachenko, O. Sotula, V. Biblenko, K. Giulyakov, O. Bereznikov // Cuestiones politicas. - V. 39. - Issue 68. - Universidad del Zulia, 2021. - Р. 441-462.
Keywords: sociocultural environment; substrate of criminal-legal influence; criminal-legal measure; coercive and incentive influence methods; judicial discretion; соціокультурне середовище; субстрат кримінально-правового впливу; кримінально-правовий захід; примусові та стимулюючі методи впливу; судовий розсуд; Research Subject Categories::LAW/JURISPRUDENCE